Inhibition of RAC1 activator DOCK2 ameliorates cholestatic liver injury via regulating macrophage polarisation and hepatic stellate cell activation - Jianli Qiu; Yitong Qu; Yinli Li; Cancan Li; Junling Wang; Lu Meng; Xiaojin Jing; Jiangping Fu; Yan Xu; Yuna Chai (Biology Direct)
Abstract Background The Rho GTPase Rac family small GTPase 1 (RAC1) is considered a promising fibrotic therapeutic target, but the role of its activator, dedicator of cytokinesis 2 (DOCK2), in liver fibrosis is largely unknown. This study aimed to investigate the expression and role of DOCK2 in cholestasis-induced liver fibrosis and to further explore the potential mechanisms. Results Cholestasis was induced in male C57BL/6 mice by bile duct ligation (BDL). DOCK2 knockdown was achieved by tail vein injection of adenovirus containing DOCK2-targeting shRNA. The effect of DOCK2 knockdown on cholestatic liver injury was evaluated at different time points after BDL. Hepatic DOCK2 expression gradually increased after BDL. Knockdown of DOCK2 reduced the necrotic area in BDL liver and downregulated serum levels of liver injury indicators. At 3d post-BDL (acute phase), DOCK2 knockdown alleviated M1 macrophage inflammation in the liver, as evidenced by reduced infiltrating iNOS + macrophages and inflammatory cytokines and mitigated NLRP3 inflammasome activation. At 14d post-BDL (chronic phase), DOCK2 knockdown suppressed hepatic stellate cell (HSC) activation and liver fibrosis as indicated by decreased α-SMA + HSCs and extracellular matrix deposition. In vitro experiments further demonstrated that DOCK2 knockdown suppressed M1 macrophage polarisation and HSC to myofibroblast transition, accompanied by inhibition of RAC1 activation. Conclusions In summary, this study demonstrates for the first time that the RAC1 activator DOCK2 regulates M1 macrophage polarisation and hepatic stellate cell activation to promote cholestasis-induced liver inflammation and fibrosis, suggesting that DOCK2 may be a potential therapeutic target in cholestatic liver injury.